Enhancing Firm Value of Palestinian Public Listed Companies through Intellectual Capital Performance and Disclosure - Ahmed Adel Mahmoud Ammar; Muhammad Iqmal Hisham Kamaruddin (EconJournals, 2025)
Indexed by Scopus (Tier 2)